2016
DOI: 10.12740/pp/44010
|View full text |Cite
|
Sign up to set email alerts
|

Compulsive buying in outline

Abstract: In spite of a hundred year long history of scientific research compulsive buying has been a hardly known phenomenon until today. Ambiguous scientific information makes it impossible to classify compulsive buying as a separate mental disorder. Recently many researchers have noticed phenomenological compatibility of compulsive buying with behavioural addictions. Nowadays, there is reasonable grounds that compulsive buying disorder can be defined as an addiction. There are many similarities occurring between a co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
0
7

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(19 citation statements)
references
References 36 publications
1
11
0
7
Order By: Relevance
“…As a consequence of this excessive behavior, individuals with PB suffer significant psychological distress and legal/financial problems (Müller, Mitchell, & de Zwaan, 2013). No consensus has been reached regarding the classification of PB (Zadka & Olajossy, 2016) did not categorize PB as a mental disorder (Piquet-Pessôa, Ferreira, Melca, & Fontenelle, 2014;Potenza, 2014). However, PB is often clinically classified as a behavioral addiction, due to its shared phenotype with other recognized behavioral addictions, such as gambling disorder (GD; Grant, Potenza, Weinstein, & Gorelick, 2010;Kellett & Bolton, 2009;Müller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…As a consequence of this excessive behavior, individuals with PB suffer significant psychological distress and legal/financial problems (Müller, Mitchell, & de Zwaan, 2013). No consensus has been reached regarding the classification of PB (Zadka & Olajossy, 2016) did not categorize PB as a mental disorder (Piquet-Pessôa, Ferreira, Melca, & Fontenelle, 2014;Potenza, 2014). However, PB is often clinically classified as a behavioral addiction, due to its shared phenotype with other recognized behavioral addictions, such as gambling disorder (GD; Grant, Potenza, Weinstein, & Gorelick, 2010;Kellett & Bolton, 2009;Müller et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Almost every independent adult, and even teenagers, engage in shopping activities. However, it has been shown that some consumers become excessively involved, which leads to several psychological, health, social and legal problems [9][10][11][12]. Studies show a relationship between excessive shopping and low well-being [12][13][14][15], sense of guilt, alienation, loneliness and marital problems [16][17][18].…”
Section: Compulsive Buyingmentioning
confidence: 99%
“…Prawie każda samodzielna dorosła osoba, a nawet nastolatkowie angażują się w aktywność zakupową. Jak się jednak dowodzi, część konsumentów angażuje się nadmiernie, co prowadzi do szeregu problemów o charakterze psychologicznym, zdrowotnym, społecznym i prawnym [9][10][11][12]. Badania wskazują na związek nadmiernego kupowania z obniżonym samopoczuciem [12][13][14][15], poczuciem winy, wyobcowania, samotności i problemami małżeńskimi [16][17][18].…”
Section: Kompulsywne Kupowanieunclassified
“…However, compulsive buying is more prevalent in females, despite the fact it also overlaps with externalizing behaviors and related traits, and evidence shows it comprises at least some of the components considered prototypical of behavioral addictions. These components include weakened control despite negative consequences, tolerance, withdrawal, and craving [ 80 82 ]. Its higher prevalence in females has been related to the observation that buying is used as an overt emotional regulation strategy to cope with or scape from negative affective states [ 28 ].…”
Section: The Role Of Gendermentioning
confidence: 99%